Health information seeking and use among rural poor families in West Java, Indonesia - Yusup , Pawit M.; Komariah , Neneng (Faculdade de Filosofia e Ciências, 2014)
The purpose of this research is to map patterns of health information need, seeking and use of deprived families in Kabupaten Bandung, West Java. This study used the survey method towards 136 people belonging to the deprived population. The results show: (1) the most prominent information need dimension is related to the basic needs comprising food, clothing, shelter (housing), health, and education, (2) the most prominent health information seeking dimension is related to seeking actively for informal interpersonal sources, and (3) the most prominent information use dimension is the type of health information acquired from selected health experts, neighbors and family as well. The main conclusion is the need for health information has not yet become a priority for the poor people, however when they need the information they will seek actively to informal information sources and they use this information to solve their health problem.